1996
DOI: 10.7557/2.16.2.1198
|View full text |Cite
|
Sign up to set email alerts
|

Fire - caribou - winter range relationships in northern Canada

Abstract: We needed data on temporal changes in caribou forages after fire and relative use of age-classes of forests by caribou to help devise a fire suppression priority strategy for caribou winter range in north-central Canada. Consequently, from 1983 through 1986, we estimated the abundance of vegetation and relative use by caribou at 197 sites in western and eastern study areas on the winter range of the Beverly herd of caribou {Rangifer tarandus). Species of lichens attained peak biomass at different periods after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 6 publications
10
52
0
Order By: Relevance
“…Fire greatly decreases the ground lichen cover in the short term (Morneau and Payette 1989;Thomas et al 1996), but the long term effects depend on the forest type. Burning of lichen-rich ground benefits shrubs and has thus significant negative effects on reindeer herding.…”
Section: Site Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire greatly decreases the ground lichen cover in the short term (Morneau and Payette 1989;Thomas et al 1996), but the long term effects depend on the forest type. Burning of lichen-rich ground benefits shrubs and has thus significant negative effects on reindeer herding.…”
Section: Site Preparationmentioning
confidence: 99%
“…The final successional phase in a plant community dominated by reindeer lichens is reached ca. 100 years after complete burning (Morneau and Payette 1989;Thomas et al 1996). However, burned areas may be used for reindeer foraging much earlier, depending on the distance to dispersal sources.…”
Section: Site Preparationmentioning
confidence: 99%
“…Additionally with the predicted increase in snow depths it will require more energy for animals to dig feeding craters. Studies of lichen abundance have been legion during the past 40 years; some of us have spent endless field days looking in feeding craters and measuring lichen abundance (Bergerud, 1974c;1971;1988;Miller, 1976;Thomas et al, 1996). No demographic impacts have been documented in these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas & Kiliaan (1998) showed that the condition of the Beverly herd in March of 8 years 1980 to 1987 was superior to the condition of caribou in the Kaminuriak Herd in early April in 3 years (1966¬ 68). The superior condition of the Beverly Herd compared to the Kaminuriak occurred despite the finding that there were reduced lichen supplies on the Beverly Herd compared to the Kaminuriak in both the 1960s and 1980s as a result of forest fires, and despite the fact that densities were 3-4 times greater for the Beverly in the 1980s than the Kaminuriak in the 1960s (Parker, 1972;Miller, 1976ab;Thomas et al, 1996, Thomas & Kiliaan, 1998. We might rank these four major herds that have been investigated as to late winter body condition (Porcupine-1980s, George River1980s, Kaminuriak-1960s, Beverly-1980s) There is no obvious relationship between snow cover, lichen abundance, animal densities or physical con¬ dition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation